2016
DOI: 10.1002/rnj.190
|View full text |Cite
|
Sign up to set email alerts
|

Examining Functioning and Contextual Factors in Individuals with Joint Contractures from the Health Professional Perspective Using the ICF: An International Internet-Based Qualitative Expert Survey

Abstract: International health professionals reported a large variety of aspects of functioning and health, which are related to joint contractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 23 publications
(28 reference statements)
0
19
0
1
Order By: Relevance
“…Joint contractures are common complications of nervous system diseases, such as stroke and spinal cord injury [1], and more than one-fth of elderly residents in long-term care (LTC) facilities suffer from joint contractures [2], resulting in functional restrictions and limitations of joint mobility and thus activity limitations and participation restrictions [2][3][4]. Many studies have noted that activity limitations and participation restrictions, such as the inability to write or inability to visit friends, are most relevant to patients with joint contractures [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Joint contractures are common complications of nervous system diseases, such as stroke and spinal cord injury [1], and more than one-fth of elderly residents in long-term care (LTC) facilities suffer from joint contractures [2], resulting in functional restrictions and limitations of joint mobility and thus activity limitations and participation restrictions [2][3][4]. Many studies have noted that activity limitations and participation restrictions, such as the inability to write or inability to visit friends, are most relevant to patients with joint contractures [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…This nding can help scholars and experts concerned about the QOL of elderly residents in LTC facilities to simplify the complex QOL connotation. Therefore, elderly individuals with joint contractures may have severely limited mobility, which could lead to participation restrictions and negatively affect their QOL [5][6][7]11].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research, using the International Classification of Functioning, Disability and Health (ICF) [8] as a framework, indicates that joint contractures are associated with numerous limitations of functioning such as mobility, self-care, sensory function and pain, domestic life and community, social and civic life [9]. Limitations on activities (i.e., "the execution of a task or action") and restrictions on participation (i.e., "the involvement in a life situation") are the most relevant problems for the affected individuals [9][10][11][12][13]. Moreover, interviews with affected individuals in geriatric care revealed that immobility does not necessarily lead to restrictions in participation, rather the restrictions are induced by environmental and personal factors [9].…”
Section: Introductionmentioning
confidence: 99%
“…Due to diverse treatment priorities, a wide range of health care professionals are involved in the care of individuals with joint contractures, for example nurses, physical and occupational therapists and physicians. The involvement of informal caregivers is also crucial [12]. A successful intervention for nursing home residents with joint contractures has to consider the interaction between joint contractures, the individuals' daily life and the influence of environmental and personal factors, and should also address all health care professionals involved in the treatment of the affected individuals [17].…”
Section: Introductionmentioning
confidence: 99%
“…Due to diverse treatment priorities, a wide range of healthcare professionals are involved in the care of individuals with joint contractures, for example nurses, physical and occupational therapists and physicians. The involvement of informal caregivers is also crucial [12]. A successful intervention for nursing home residents with joint contractures has to consider the interaction between joint contractures, the individuals' daily life and the in uence of environmental and personal factors, and should also address all healthcare professionals involved in the treatment of the affected individuals [17].…”
mentioning
confidence: 99%